Geranium Aralia, Polyscias guilfoylei (W. Bull) L.H. Bailey), Leaf Extract Toxicity against Melon Fly, Zeugodacus cucurbitae Coquillett - Rachmawati, Jeti; Martono, Edhi; Trisyono, Y. Andi (Jurnal Perlindungan Tanaman Indonesia, 2023)
Zeugodacus cucurbitae Coquillett is one of the most detrimental pests that mostly attack family Cucurbitaceae. Control over this pest often uses insecticides, and one of the plants with the potentiality to be used as source of insecticide is Polyscias guilfoylei. This research aimed to study the influence of P. guilfoylei leaf extract application upon Z. cucurbitae mortality and to determine the LC50 value. The research was conducted at Pest Invertebrate Plant Pest Science Laboratory, Department of Plant Protection, Faculty of Agriculture, Universitas Gadjah Mada. The toxicity test was done using contact, oral and residue methods upon ethanol and n-hexane extracts with 0; 1.25; 2.50; 5.00; 10.00; and 20.00% concentrations. The research used randomized group design with six replications. The parameters observed were the number of dead melon fly at 72 hours after the treatment and LC50 value of each extract. The data were analyzed using Probit analysis via 1.02 version of Lenora software Polo Plus. The result shows that ethanol and n-hexane extracts of P. guilfoylei leaf using oral and residue methods affected Z. cucurbitae mortality. However, in contact method, ethanol and n-hexane extracts of P. guilfoylei leaf did not affect Z. cucurbitae mortality. LC50 values of ethanol extract using oral and residual methods were 6.168% and  3.658%, respectively. LC50 values of n-hexane extract using oral and residual method reached 5.311% and 6.607%, respectively. This research shows that ethanol and n-hexane extracts of P. guilfoylei leaf contain secondary metabolites that are toxic for melon fly Z. cucurbitae.